1993
DOI: 10.1037/0278-6133.12.3.227
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making orientation and AIDS-related knowledge, attitudes, and behaviors of Hispanic, African-American, and White adolescents.

Abstract: How adolescents' personal sense of directedness (i.e., peer, parent, or self-directed orientation) affects the decision-making processes of adolescent students regarding AIDS-related knowledge, attitudes, beliefs, behaviors, and skills (KABBS) is examined. The sample consisted of 10th-grade students in 8 public high schools (N = 2,515) in Dade County (greater Miami), Florida. The findings showed that decision-making orientation and directedness was a significant predictor of AIDS-related KABBS of adolescents. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 35 publications
(40 reference statements)
0
8
0
1
Order By: Relevance
“…Because young people value sexual activity as a sign of maturity [19], peer orientation may be a particularly powerful source of risk in this domain. Indeed, previous research has found peer orientation to be associated with risky sexual attitudes and behavior [21]. Although a connection between self-pride and peer orientation has not been established in the literature, we hypothesize that a positive self-image will render adolescents less likely to conform to perceived peer norms by adopting risky sexual attitudes and behaviors.…”
Section: Youth Mediatorsmentioning
confidence: 95%
“…Because young people value sexual activity as a sign of maturity [19], peer orientation may be a particularly powerful source of risk in this domain. Indeed, previous research has found peer orientation to be associated with risky sexual attitudes and behavior [21]. Although a connection between self-pride and peer orientation has not been established in the literature, we hypothesize that a positive self-image will render adolescents less likely to conform to perceived peer norms by adopting risky sexual attitudes and behaviors.…”
Section: Youth Mediatorsmentioning
confidence: 95%
“…Previous work has shown the importance of targeting high sensation-seeking individuals when delivering successful mass media messages focusing on risk behavior such as substance abuse, 22,[23][24][25][26] and of focusing on impulsive decision makers when designing messages related to risky sexual behavior. 27 Consequently, we conclude that it might also be important to target these groups in the design of HIV and pregnancy prevention classroom interventions. In this article, we assess whether adapting a successful school-based curriculum to meet the needs of these individuals improves its effectiveness in promoting safer behaviors.…”
mentioning
confidence: 95%
“…Past research on early adolescent sexual decision making focused on two major decision points: whether or not to engage in sexual intercourse and whether or not to use safer sex methods, such as condoms (Hulton, 2001). Quantitative studies identified risk and protective factors that appear to influence adolescents' decisions to engage in sexual activity or to use safer sex methods, including self-efficacy, parental values, peer norms, supervision, decision-making orientation, and partner communication (e.g., Cohen, Farley, Taylor, Martin, & Schuster, 2002;DiIorio, Dudley, Kelly, Soet, Mbwara, & Sharpe Potter, 2001;DiIorio, Dudley, Soet, & McCarty, 2004;Epstein, Dusenbury, Botvin, & Diaz, 1994;Jensen, de Gaston, & Weed, 1994;Langer, Zimmerman, Warheit, & Duncan, 1993;Longmore, Manning, Giordano, & Rudolph, 2003;Paikoff, 1995;Rosenthal, von Ranson, Cotton, Biro, Mills, & Succop, 2001;Sieving, Resnick, Bearinger, Remafedi, Taylor, & Harmon, 1997).…”
mentioning
confidence: 99%